STUDI IMPLEMENTASI SUPER BRAIN MEMORY DALAM MENGHAFAL AL-QUR’AN HADITS DI MADRASAH ALIYAH NEGERI BANGIL - Saadah Saadah (JIE (Journal of Islamic Education), 2017)
The purpose of this study was to determine the concept of super brain learning memory in memorizing the Qur'an Hadith, implementation, and results of its implementation in MAN Bangil with the type of field research using fenomonologis approach. Then the data that has been analyzed by using inductive method, while the technique of data analyzed using theory of miles and Hunberman, the problems experienced in its implementation, namely in terms of strategy or good teaching and learning system that timing, management class, which would cause a problem for students, less precise in placing between the classical stage and the private stage, resulting in a shortage of time, which will result in the implementation of the other phases, which should all stages can be implemented properly